2021
DOI: 10.3390/jdb9040047
|View full text |Cite
|
Sign up to set email alerts
|

The Organizer and Its Signaling in Embryonic Development

Abstract: Germ layer specification and axis formation are crucial events in embryonic development. The Spemann organizer regulates the early developmental processes by multiple regulatory mechanisms. This review focuses on the responsive signaling in organizer formation and how the organizer orchestrates the germ layer specification in vertebrates. Accumulated evidence indicates that the organizer influences embryonic development by dual signaling. Two parallel processes, the migration of the organizer’s cells, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 156 publications
1
18
0
3
Order By: Relevance
“…Moreover, the inhibition of FGF signaling recovered the activin-reduced expression of ventral mesodermal markers in DMZ, including ventx1.1 , gata2 , and α-globin . Furthermore, FGF inhibition in DMZ induced ventx1.1 expression to eliminate the expression of the organizer and dorsal-mesodermal-specific markers, including chordin and noggin , in the gastrulae [ 73 , 74 , 75 ]. These studies have suggested that Ventx1.1 is involved in ventral mesodermal formation and hematopoiesis in Xenopus .…”
Section: Ventx Family In Xenopusmentioning
confidence: 99%
“…Moreover, the inhibition of FGF signaling recovered the activin-reduced expression of ventral mesodermal markers in DMZ, including ventx1.1 , gata2 , and α-globin . Furthermore, FGF inhibition in DMZ induced ventx1.1 expression to eliminate the expression of the organizer and dorsal-mesodermal-specific markers, including chordin and noggin , in the gastrulae [ 73 , 74 , 75 ]. These studies have suggested that Ventx1.1 is involved in ventral mesodermal formation and hematopoiesis in Xenopus .…”
Section: Ventx Family In Xenopusmentioning
confidence: 99%
“…In Xenopus , Nodal signaling from the vegetal region and Wnt signaling at the dorsal region contribute to determine the organizer region (De Robertis et al, 2000). Bmp antagonists such as Chrd.1, Nog, and Fst are expressed in the organizer region to inhibit Bmp activities and produce the chordamesodermal axis (Kumar et al, 2021). Suppression of Bmp signaling is required for neural induction, and the expression of cement gland‐inducer genes such as pitx1 requires an intermediate level of Bmp signaling (Jin & Weinstein, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bmp inhibition or the activation of Nodal signaling alone on the ventral side during early developmental stage does not result in complete axis formation including the head (Suzuki et al, 1994). Moreover, other organizer genes such as dkk1 , cer1 , and frzb inhibit Wnt activities in the mesendodermal region in order to produce head structures (De Robertis & Kuroda, 2004; Kumar et al, 2021). In zebrafish, ccr7 was found to induce Ctnnb1 degradation, which inhibited axis formation, upregulated bmp4 expression, and downregulated chrd.1 expression (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Xenopus , gastrulation is a critical event that allows germ layer formation and embryonic patterning [ 1 , 2 , 3 ]. During this process, the dorsal mesoderm or organizer-specific Goosecoid (Gsc) plays an essential role in initiating inductive signaling to trigger dorso-anterior migration from the dorsal lip of the blastopore [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%